Wetu Telu Culture as the Basis for Transformative Islamic Education in the Global Era: A Case Study in Lombok Utara - Nurmalayani, Ayu; Wijoyo, Dwi Fitri (Journal of Educational Sciences, 2025)
The era of globalization, marked by rapid developments in information and technology, can shift the values that grow and develop within society. This shift in values presents a unique challenge in the increasingly complex world of education. This study aims to critically and in-depth explore and analyze the values that have grown, developed, and been embraced by the Bayan community within the Wetu Telu culture as the foundation for transformational Islamic education. The research method used in this study is a descriptive qualitative approach. Data collection was conducted through observation, interviews, and documentation, followed by data processing through three stages: data reduction, data presentation, and conclusion-drawing mechanisms. This study found that within Wetu Telu culture, educational values are expressed symbolically in every traditional ceremony and ritual practice. These values align with Islamic teachings and educational ideals such as faith, morals, and worship. These values are actualized to foster a moderate and inclusive perspective. Educational values rooted in local cultural wisdom and integrated with Islamic teachings are relevant as foundations for transformational Islamic education in the current global era.